Optimization of Antimicrobial Photodynamic Therapy in Biofilms by Inhibiting Efflux Pump - De Aguiar Coletti, Tatiana Maria Starck Fogaça [UNESP]; De Freitas, Laura Marise [UNESP]; Almeida, Ana Marisa Fusco [UNESP]; Fontana, Carla Raquel [UNESP] (SAGE Publications, 2017)
Background: One of the main mechanisms of microbial resistance is given by efflux pumps, which reduce the effectiveness of antimicrobials by decreasing their intracellular concentration. Objective and methods: Considering that efflux pump inhibitors are promising adjuvant molecules for antibiotics in infections, in this study, using XTT test and colony forming unit (CFU) counting, we evaluated the association between the pump inhibitor verapamil (VP) and the antimicrobial photodynamic therapy (aPDT) mediated by methylene blue (MB) in biofilms of Escherichia coli and Staphylococcus aureus to optimize the bacterial reduction. Results: By applying 44 J/cm2, 215 μg/mL of VP, and 200 μg/mL of MB, we obtained 80% of metabolism reduction and 3.4 log10 CFU/mL decrease for E. coli. Biofilm of S. aureus presented 80% of metabolism reduction and 3.65 log10 CFU/mL decrease when 22 J/cm2, 312 μg/mL of VP, and 200 μg/mL of MB was used. Applying 200 μg/mL of MB, the E. coli biofilm required a higher dose of light, while the S. aureus biofilm required a higher concentration of VP to obtain the same reduction. Conclusions: The VP optimized the efficiency of aPDT and showed no toxicity when used alone in both strains, proving that inhibiting efflux pumps in combination with aPDT has great potential for clinical application.
Keywords: antimicrobial photodynamic therapy; biofilms; efflux pump; methylene blue